2013
DOI: 10.1007/s00038-013-0496-8
|View full text |Cite
|
Sign up to set email alerts
|

Health effects associated with the disposal of solid waste in landfills and incinerators in populations living in surrounding areas: a systematic review

Abstract: A moderate level of confidence is possible in limited areas of knowledge, implying the need to overcome the limitations of current studies about exposure assessment and to control confounders at the individual level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 67 publications
8
61
1
2
Order By: Relevance
“… 26 Occurrence of respiratory symptoms was documented among residents living close to waste sites 12 and was linked to inhalation exposure to endotoxin, microorganisms, and aerosols from waste collection and land filling. 27 …”
Section: Discussionmentioning
confidence: 99%
“… 26 Occurrence of respiratory symptoms was documented among residents living close to waste sites 12 and was linked to inhalation exposure to endotoxin, microorganisms, and aerosols from waste collection and land filling. 27 …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the lack of accurate information on exposure levels represents undoubtedly the major issue in the evaluation of waste management-related health impacts [10]. More in general, previous studies outlined that the exposure assessment often represented the main uncertainty in epidemiological studies, mainly due to inadequate methods, which introduced misclassification of exposure with a consequent decrease in the likelihood of detecting significant exposure-effect associations [1,12,13]. Future studies in this field should require improvement in the characterization of individual exposures; in this regard, one of the most promising progresses in the exposure science is the development of miniaturized instruments for participatory and ubiquitous monitoring strategies for airborne pollutants [16].…”
Section: Exposure Assessment In Studies On Health Impact Of Waste Manmentioning
confidence: 99%
“…Similarly, Barba et al concluded that the available evidence suffers from limitations mainly due to study design, lack of consideration of confounders and quality of the exposure data [11]. Thus, although many studies and reviews are available, the lack of adequate and accurate data on exposure levels represents one of the major issue in the evaluation of health effects arising from exposure to waste management processes [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These sites provide a ready source of nutrition and shelter for human-introduced species that support the spread of pathogen vectors and non-native/invasive species (Rusterholz et al, 2012), while discarded pollutants can disperse across the landscape (Diletti et al, 2008;Mattiello et al, 2013). As a consequence, illegal waste sites pose serious economic and social challenges through an increased burden upon the public health system (Ashworth et Many publications refer to the influence of specific chemicals or chemical mixtures in illegal landfills on human health (Baibergenova et al, 2003;Kramer, 1987;Sorsa et al, 1992;Sullivan, 1993) but there are almost no data about their influence on biotic homogenisation and the spread of pathogens throughout the rodents living area.…”
Section: Introductionmentioning
confidence: 99%